Poglądy legislatorów Polski stanisławowskiej na zasadę równości w projektach reform praw kryminalnych - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is devoted to the reform of criminal law in 18th-century Poland and is one of the effect of many years of research in the field. In analysing selected views, draft legislation and legal regulations from the reign of the last king of Poland, the author focuses on the polemic surrounding the principle of equality in criminal law in an estate country. At the same he tries to note similarities and differences in the views of legislators of the Enlightenment period, exploring the reasons for and the nature of the divergencies in their positions
Keywords: prawo cywilne; Stanisław August Poniatowski (król Polski; 1732-1798); Wybicki, Józef (1747-1822); prawo karne